Oldowan Technology Amid Shifting Environments ∼2.03–1.83 Million Years Ago - Cueva-Temprana, Arturo; Lombao, Diego; Soto, María; Itambu, Makarius; Bushozi, Pastory; Boivin, Nicole; Petraglia, Michael; Mercader, Julio (Frontiers in Ecology and Evolution, 2022)
The Oldowan represents the earliest recurrent evidence of human material culture and one of the longest-lasting forms of technology. Its appearance across the African continent amidst the Plio-Pleistocene profound ecological transformations, and posterior dispersal throughout the Old World is at the foundation of hominin technological dependence. However, uncertainties exist concerning the degree to which the Oldowan constitutes an environment-driven behavioral adaptation. Moreover, it is necessary to understand how Oldowan technology varied through time in response to hominin ecological demands. Here we present the stone tool assemblage from Ewass Oldupa, a recently discovered archaeological site that signals the earliest hominin occupation of Oldupai Gorge (formerly Olduvai) 2.03 Ma. At Ewass Oldupa, hominins underwent marked environmental shifts over the course of a 200 kyr period. In this paper, we deployed an analysis that combines technological and typological descriptions with an innovative quantitative approach, the Volumetric Reconstruction Method. Our results indicate that hominins overcame major ecological challenges while relying on technological strategies that remained essentially unchanged. This highlights the Oldowan efficiency, as its basic set of technological traits was able to sustain hominins throughout multiple environments.